2009
DOI: 10.1103/physrevlett.103.175003
|View full text |Cite
|
Sign up to set email alerts
|

Electron Self-Injection in Multidimensional Relativistic-Plasma Wake Fields

Abstract: We present an analytical model for electron self-injection in a nonlinear, multidimensional plasma wave excited by a short laser pulse in the bubble regime or by a short electron beam in the blowout regime. In these regimes, which are typical for electron acceleration, the laser radiation pressure or the electron beam charge pushes out background plasma electrons forming a plasma cavity--bubble--with a huge ion charge. The plasma electrons can be trapped in the bubble and accelerated by the plasma wakefields u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 28 publications
6
128
0
Order By: Relevance
“…2(f) gives p z max ≈ 21m e c > γ g m e c,a n d|p r max |≈4m e c. The large longitudinal momentum of these electrons makes them the best injection candidates; their promotion to fully dynamic macroparticles may result in their self-injection and acceleration (Morshed et al, 2010). Longitudinal synchronization of sheath electrons, p z ≥ γ g m e c, is necessary and, in highdensity plasmas (such as γ g ≈ k p R b ), also sufficient for their injection (Kostyukov et al, 2009). In the opposite limit of strongly rarefied plasmas, γ g > 10k p R b , the sheath electrons do not synchronize with (and thus cannot be injected into) a non-evolving bubble (i.e.…”
Section: Injection Candidates Collection Volume and Minimal Expansimentioning
confidence: 99%
“…2(f) gives p z max ≈ 21m e c > γ g m e c,a n d|p r max |≈4m e c. The large longitudinal momentum of these electrons makes them the best injection candidates; their promotion to fully dynamic macroparticles may result in their self-injection and acceleration (Morshed et al, 2010). Longitudinal synchronization of sheath electrons, p z ≥ γ g m e c, is necessary and, in highdensity plasmas (such as γ g ≈ k p R b ), also sufficient for their injection (Kostyukov et al, 2009). In the opposite limit of strongly rarefied plasmas, γ g > 10k p R b , the sheath electrons do not synchronize with (and thus cannot be injected into) a non-evolving bubble (i.e.…”
Section: Injection Candidates Collection Volume and Minimal Expansimentioning
confidence: 99%
“…Previous works [15,16] have shown using a phenomenological non-evolving spherical bubble model that trapping is possible for large enough blowout radii, where the critical blowout radius for trapping scales linearly with the bubble relativistic factor γ 0 . Other authors [17] have found empirically (from PIC simulations) that when the radius exceeds several collisionless skip depths trapping always occurs for non-evolving bubbles regardless of the bubble velocity.…”
Section: Trapping In a Non-evolving Bubblementioning
confidence: 99%
“…There have been several numerical studies of this trapping process [29,30], which predict density thresholds for self-trapping of few-10 18 -10 20 cm −3 for the blowout condition 2<a 0 <4. This thesis will present data indicating that in He plasmas this threshold occurs at 4x10 18 cm −3 for laser powers of 60 TW.…”
Section: Self-injectionmentioning
confidence: 99%